Coronary Syndrome: Clinical Treatment, Prevention and Management for Better Outcomes - Node, Koichi; Tanaka, Atsushi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on recent advances in the clinical care of patients with acute and chronic coronary syndromes. We must accumulate novel scientific and clinical knowledge in this field to develop seamless treatments and preventive strategies for this patient population. Furthermore, accumulated data have implicated that there are some residual risk factors for coronary syndromes, and the clinical management of cardiovascular/non-cardiovascular complications associated with coronary syndromes is also a critical concern. We hope that this reprint will facilitate the management of future patients with coronary syndromes; however, further research is still required. It is also our hope that this reprint will promote future research to enable a better understanding of the clinical practice of coronary syndromes.